The Effect of Profitability and Green Accounting on Earnings Management in Companies on the Indonesia Stock Exchange (IDX) during Covid 19 Pandemic - Simpati Mellyginta Sibuhaji; May Hana Bilqis Rangkuti (Journal Of Management Analytical and Solution (JoMAS), 2024)
The Covid 19 pandemic has been going on for the past three years. There have been many changes that have occurred in human life at this time. The Covid 19 pandemic has not only disrupted the health sector, but also disrupted the economic sector. The existence of restrictions on social activities and regional quarantine has hampered economic activity so that it has an impact on business activities which has worsened the level of profitability and economic growth of companies, especially in Indonesia. Not to mention that companies have to pay more attention to Green Accounting due to the prolonged pandemic. The budgets of these companies related to Green Accounting will certainly affect the financial statements of these companies. This of course can affect the performance of existing financial reports in companies that will be related to earnings management of a company. The implementation of earnings management will also affect internal and external parties of the company. Earnings management is an action taken by company management to influence reported earnings which can provide information about economic benefits to both internal and external parties. Where earnings management is a central issue and has become a common phenomenon that occurs in a number of companies today. Earnings management practices have increased every year until now.